Fragilidade Ambiental nas áreas periurbanas de Sorocaba: análise das mudanças no uso da terra entre 2016 e 2022 - Almeida, Vinícius Bianco Fogaça de (Universidade Federal de São Carlos, 2024)
This study analyzes environmental fragility in the peri-urban areas of Sorocaba between 2016 and 2022, aiming to identify and categorize vulnerability areas as a function of urban expansion. The methodology employed the classification of environmental variables, such as pedology, geology, slope, and land use, applying weighted values to determine fragility classes, following an adaptation of Ross’s model. The study produced comparative maps of fragility levels for the analyzed years, demonstrating a reduction in low-fragility areas and an increase in medium and high-vulnerability zones. This mapping provides a basis for urban planning decisions, highlighting the importance of preserving areas with high potential for environmental resilience.
Português
Keywords: fragilidade ambiental; cobertura e uso da terra; urbanização; periurbano; environmental fragility; land cover and use; urbanization; peri-urban; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS::GEOGRAFIA FISICA::GEOECOLOGIA